2001
DOI: 10.1051/0004-6361:20010314
|View full text |Cite
|
Sign up to set email alerts
|

Incompatibility of a comoving Lyαforest with supernova-Ia luminosity distances

Abstract: Recently, Perlmutter et al. (1999) suggested a positive value of Einstein's cosmological constant Λ on the basis of luminosity distances from type-Ia supernovae (the "SN-method"). However, Λ world models had earlier been proposed by Hoell & Priester (1991) and Liebscher et al. (1992a,b) on the basis of quasar absorption-line data (the "Q-method"). Employing more general repulsive fluids ("dark energy") encompassing the Λ component, we quantitatively compare both approaches. Fitting the SN-data by a minimum-com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…We will not go over this material in detail here; recent reviews may be found in [107] and [142]. Instead, we will approach the phenomenon of quasar absorption lines in a different way and focus on what is probably the "Achilles heel" of the BN-P approach: its assumption that intrinsic evolution in the absorber population can be neglected relative to the Hubble expansion rate.…”
Section: Quasar Observermentioning
confidence: 99%
See 1 more Smart Citation
“…We will not go over this material in detail here; recent reviews may be found in [107] and [142]. Instead, we will approach the phenomenon of quasar absorption lines in a different way and focus on what is probably the "Achilles heel" of the BN-P approach: its assumption that intrinsic evolution in the absorber population can be neglected relative to the Hubble expansion rate.…”
Section: Quasar Observermentioning
confidence: 99%
“…The study of these issues occupied most of the last ten years of Wolf's career, including two more review articles in Naturwissenschaften, a chapter in the authoritative Bergmann-Schaefer Lehrbuch der Experimentalphysik and many more publications [94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109]. We will not go over this material in detail here; recent reviews may be found in [107] and [142]. Instead, we will approach the phenomenon of quasar absorption lines in a different way and focus on what is probably the "Achilles heel" of the BN-P approach: its assumption that intrinsic evolution in the absorber population can be neglected relative to the Hubble expansion rate.…”
Section: Quasar Observermentioning
confidence: 99%
“…1(b). We do not discuss the details of this model here (see Liebscher, Kayser and Helbig, 1996;Thomas and Schulz 2001 for critical reviews), except to note that it was derived from Lyα absorption-line statistics under the assumption that evolutionary effects could be neglected. Insofar as this assumption is justified, the present results can be seen as a confirmation of this earlier work, which was based on a significantly older dataset and a completely independent method of analysis.…”
Section: Cosmology Vs Evolutionmentioning
confidence: 99%